Financial Capability in Low- and Middle-Income Countries : Measurement and Evaluation - Holzmann, Robert; Mulaj, Florentina; Perotti, Valeria (World Bank, Washington, DC, 2013)
This report provides an overview of the conceptual foundations and work program implemented by the World Bank under the Russia Financial Literacy and Education Trust Fund (RTF) generously supported by the Ministry of Finance of the Russian Federation beginning in October 2008. The overall objective of the Trust Fund was to support implementation of the December 2006 summit statement from the Russian G8 Presidency, which greatly advanced the topic of financial literacy and education within the international policy discussion. The specific objective of the overall effort was to extend the knowledge base to help Low-Income Country's (LICs) and Middle-Income Country's (MICs) prepare and implement national strategies and programs in this area. This report positions the results of the RTF work program undertaken by the World Bank within the broader realm of international knowledge activities. It highlights the contributions of this work program to the conceptual development and measurement of financial capability and the evaluation of the results achieved by programs directed towards its enhancement. The elements of the work program led by the World Bank focused on two measurement-related topics: 1) how to measure financial capability in a way that is applicable to diverse levels of economic development and across individuals of different income levels; and 2) how to measure the effectiveness of interventions to improve financial capability including, but extending well beyond, formal financial education programs.